Study of Regional Left Ventricular Longitudinal Function in Fetuses with Gestational Diabetes Mellitus by Velocity Vector Imaging. Issue 8 (26th July 2016) - Wang, Xiaoyan; Lian, Yajun; Wang, Xiaofang; Tian, Min
Abstract : Objective: The purpose of this study was to investigate the clinical value of velocity vector imaging in the assessment of regional left ventricular longitudinal function in fetuses with gestational diabetes mellitus. Methods: Digital dynamic four‐chamber views of 98 fetuses with gestational diabetes mellitus and 135 normal fetuses were collected and analyzed using velocity vector imaging. The regional tissue velocity, strain, and strain rate of the interventricular septum and left lateral wall were separately measured in systole and diastole. Results: A total of 207 of 233 cases were analyzed successfully. Vs (systolic velocity) and Vd (diastolic velocity) were age‐dependent and gradually decreased from the basal segment to the apical segment in the left ventricle (P < 0.05). The Vs after 32 +0 weeks, Vd after 28 +0 weeks, and S (strain), SRs (systolic strain rate), and SRd (diastolic strain rate) after 24 +0 weeks in the left ventricle of fetuses with GDM were obviously lower than the corresponding parameters of normal fetuses (P < 0.05). Conclusion: VVI can evaluate the fetal regional left ventricular longitudinal function.